2009
DOI: 10.1002/art.24338
|View full text |Cite
|
Sign up to set email alerts
|

Understanding why rheumatoid arthritis patient treatment preferences differ by race

Abstract: Background Rheumatoid arthritis (RA) patient preferences may account for some of the variability in treatment amongst different racial groups. How and why treatment preferences differ by race is not well understood. We sought to determine whether Black and White RA patients differ in how they evaluate the specific risks and benefits related to medications. Methods 136 RA patients completed a conjoint analysis interactive computer survey to determine how they valued the specific risks and benefits related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
56
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 111 publications
12
56
0
3
Order By: Relevance
“…These results are consistent with RA patients being concerned with the total amount of time spent receiving treatment. These results are also consistent with previous studies' findings that treatment frequency and mode of administration may be at least as important as treatment response rate and the risk of treatment-related side effects (7)(8)(9). However, by varying frequency and duration independently in the experimental design, our study was the first that allowed the estimation of preferences for both of these treatment attributes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with RA patients being concerned with the total amount of time spent receiving treatment. These results are also consistent with previous studies' findings that treatment frequency and mode of administration may be at least as important as treatment response rate and the risk of treatment-related side effects (7)(8)(9). However, by varying frequency and duration independently in the experimental design, our study was the first that allowed the estimation of preferences for both of these treatment attributes.…”
Section: Discussionsupporting
confidence: 92%
“…Three previous conjoint analyses of patient preferences for RA treatments found that the mode and frequency of administration matter to RA patients and may be at least as important as treatment response rate and the risk of treatment side effects (7)(8)(9). All 3 of these studies measured preferences for combinations of mode of administration and treatment frequency, but none of the studies evaluated patients' preferences for treatment duration or their willingness to trade off between treatment duration and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is also consistent with preferencebased studies in RA that observed the primacy of treatment effectiveness over other outcomes such as safety, convenience, and cost (23,24). Novel findings from this study show that greater disease durations and experiences with various drug treatments are associated with stronger preferences for improved participation and older child age is associated with a stronger preference for reduced pain.…”
Section: Discussionsupporting
confidence: 89%
“…Despite a number of published studies examining patients' preferences for drug treatments in rheumatoid arthritis (RA) (21)(22)(23)(24)(25)(26)(27)(28)(29), few have looked at parents' preferences for drug treatments in JIA. Barron et al (30) focused on parents' preferences for nonsteroidal antiinflammatory drug (NSAID) treatments in JIA, using contingent valuation to examine parents' willingness to pay for a drug that leads to remission over one that eliminates gastrointestinalrelated side effects.…”
Section: Introductionmentioning
confidence: 99%
“…There is an urgent need to develop the evidence base to support developments in transitional care (1). We therefore welcome the article by Scal et al on transition counseling recently published in Arthritis Care & Research (2).…”
mentioning
confidence: 98%